2021
DOI: 10.3390/ijms22052499
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Allogeneic Bone-Marrow-Derived and Umbilical Cord Blood-Derived Mesenchymal Stem Cells to Prevent the Development of Osteoarthritis in An Equine Model

Abstract: Osteoarthritis (OA) is a significant cause of pain in both humans and horses with a high socio-economic impact. The horse is recognized as a pertinent model for human OA. In both species, regenerative therapy with allogeneic mesenchymal stem cells (MSCs) appears to be a promising treatment but, to date, no in vivo studies have attempted to compare the effects of different cell sources on the same individuals. The objective of this study is to evaluate the ability of a single blinded intra-articular injection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 66 publications
0
15
0
1
Order By: Relevance
“…Indeed, beyond the chondrogenic differentiation potential of MSCs, their secretome could be a therapeutic alternative. MSC injection in the equine model led to a reduction in the progression of OA [ 11 ]. Nevertheless, concomitantly with allogeneic MSCs or even autologous injections, and despite their immunomodulatory properties, MSCs can stimulate innate immune responses which can result in deleterious inflammatory reactions [ 10 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, beyond the chondrogenic differentiation potential of MSCs, their secretome could be a therapeutic alternative. MSC injection in the equine model led to a reduction in the progression of OA [ 11 ]. Nevertheless, concomitantly with allogeneic MSCs or even autologous injections, and despite their immunomodulatory properties, MSCs can stimulate innate immune responses which can result in deleterious inflammatory reactions [ 10 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond their differentiation capacities, MSCs are able to secrete a large variety of soluble mediators and extracellular vesicles (EVs), known as the cell secretome, which participates in their most relevant physiological functions, including tissue repair and immunomodulation [ 5 , 6 ]. Indeed, several in vivo studies have shown that intra-articular injections of MSCs can promote the repair of chondral defects and/or reduce inflammation [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The osteochondral fragment model used in this study has been shown to produce reliable post-traumatic OA in the middle carpal joint of horses ( 1 , 36 38 ). The mitigating effect of MSC treatment on the development of post-traumatic OA has been shown in a number of equine studies, although in different models, such as an osteochondral fragment model of the fetlock ( 39 , 40 ) a blunt impact model of the tarsus ( 15 ) and injection of the irritant amphotericin B ( 41 ). In these studies, the MSC-treated horses developed significantly less severe OA over time compared to the untreated control horses in terms of decreased synovial effusion and a higher SF viscosity and glycosaminoglycan content, decreasing lameness over time, less severe macroscopic cartilage erosions, less radiographic signs of OA, and less histologic cartilage fibrillation and subchondral sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study Lélia Bertoni and co‐workers in France evaluated allogeneic bone‐marrow‐derived and umbilical cord blood‐ derived mesenchymal stem cells (MSCs) to prevent the development of osteoarthritis (OA) in an equine model .…”
Section: Osteoarthritis Prevention Using Mscsmentioning
confidence: 99%